Experiencing Change: A Phenomenological Study of Employee Adaptation to AI-Driven Digital Transformation in a Tech Company - Dipoatmodjo, Tenri Sayu Puspitaningsih (International Humanity Advance, Business & Sciences, 2025)
The rapid advancement of Artificial Intelligence (AI) technologies has triggered significant digital transformation across industries, leading to profound changes in organizational structures, workflows, and employee experiences. This study explores how employees in a tech company experience and adapt to AI-driven digital transformation. Utilizing a phenomenological research design, in-depth interviews were conducted with selected participants to capture the lived experiences of adapting to technological change. Thematic analysis was employed to identify recurring patterns, challenges, and strategies of adaptation. Findings reveal that while employees generally perceive AI as a tool to enhance productivity and decision-making, they also express anxiety regarding job security, skill relevance, and organizational communication. Key adaptation themes include continuous learning, collaborative work culture, and psychological readiness for change. The study is grounded in theories such as sensemaking (Weick, 1995) and the Technology Acceptance Model (TAM), providing a nuanced understanding of employee behavior in the face of digital disruption. This research contributes to the growing discourse on human-centered digital transformation by emphasizing the importance of emotional, cognitive, and social dimensions of change. Practical implications include the need for targeted change management interventions and leadership strategies to foster employee engagement and resilience. The study offers valuable insights for organizations navigating AI integration, ensuring that technological advancement aligns with employee well-being and organizational sustainability.